Multi-method diet analysis to investigate lobster predation on the barren-forming sea urchin Centrostephanus rodgersii - Jennifer E Smith; John Keane; Michael Oellermann; Caleb Gardner; Craig Mundy (PANGAEA, 2023)
In Tasmania, Australia, the government extquotesingles response to range-extending, barren-forming longspined sea urchin (Centrostephanus rodgersii) includes rebuilding of southern rock lobster (Jasus edwardsii) stocks to increase predation. But lobster preference for native species and continued barren expansion challenge the control efficacy. Therefore, this study aimed to determine the impact of lobster predation on C. rodgersii in different coastal habitats using a multi-method dietary analysis comprising 1) stomach contents analysis, 2) targeted DNA detection of prey species in faecal samples and 3) stable isotope analysis (d13C and d15N). The dataset contains diet information from 64 southern rock lobster (Jasus edwardsii) from five sites (four habitat types) in eastern Tasmania, Australia. Investigated prey species included: range-extending longspined sea urchins (Centrostephanus rodgersii), Shortspined sea urchin (Heliocidaris erythrogramma), periwinkle (Lunella undulata) and blacklip abalone (Haliotis rubra).